13.74+0.13(x+3)=14.24-0.09x

Simple and best practice solution for 13.74+0.13(x+3)=14.24-0.09x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13.74+0.13(x+3)=14.24-0.09x equation:


Simplifying
13.74 + 0.13(x + 3) = 14.24 + -0.09x

Reorder the terms:
13.74 + 0.13(3 + x) = 14.24 + -0.09x
13.74 + (3 * 0.13 + x * 0.13) = 14.24 + -0.09x
13.74 + (0.39 + 0.13x) = 14.24 + -0.09x

Combine like terms: 13.74 + 0.39 = 14.13
14.13 + 0.13x = 14.24 + -0.09x

Solving
14.13 + 0.13x = 14.24 + -0.09x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.09x' to each side of the equation.
14.13 + 0.13x + 0.09x = 14.24 + -0.09x + 0.09x

Combine like terms: 0.13x + 0.09x = 0.22x
14.13 + 0.22x = 14.24 + -0.09x + 0.09x

Combine like terms: -0.09x + 0.09x = 0.00
14.13 + 0.22x = 14.24 + 0.00
14.13 + 0.22x = 14.24

Add '-14.13' to each side of the equation.
14.13 + -14.13 + 0.22x = 14.24 + -14.13

Combine like terms: 14.13 + -14.13 = 0.00
0.00 + 0.22x = 14.24 + -14.13
0.22x = 14.24 + -14.13

Combine like terms: 14.24 + -14.13 = 0.11
0.22x = 0.11

Divide each side by '0.22'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -8(2b+3)+(17b-8)=0 | | x=15*2x | | g=6xy | | 13(x-4)=-5-8 | | v=-2000+23000 | | v=-2000+2300 | | -6(5x-2)=8+4 | | -1+45x=23x+135 | | 7w-14w=1-50+49 | | 4.8q-2.9-5.1q=-1.3q-1.2 | | -4(x+1)+5x=12 | | 5c+4+3-2c= | | 33n+60=21n | | 0=3x^2+6x-297 | | 3(5x)+-2(5)=2 | | 1p-1=4p+17 | | 6y+2=8y-14 | | 2(x+9)=36 | | 2x(x)+10x+8=0 | | 7x+140=x+5 | | 2x(x-2)=16x^2-5x | | 3(4z+5)=-3z-60 | | -3y+9=-4y+2 | | 72-4n=-22 | | -2v^2-v+12=-3v^2+6w | | 2(x-2)=16x^2-5x | | 12x-8=36x+10 | | 9n-2=7n+5 | | x-3=2x+2 | | 3x-(2x+4)=4x-49 | | 8x+5x-63=42-8x | | 3(x-2)+3-2x=1 |

Equations solver categories